Aktivitas Antidiabetes Serbuk Semut Jepang (Tenebrio molitor Linn.) pada Mencit Swiss Webster Jantan yang Diinduksi Aloksan - Erwin Samsul; Andreanus A. Soemardji; Siti Kusmardiyani (Jurnal Sains dan Kesehatan, 2020)
Diabetes mellitus is a disease caused by metabolic disorders with hyperglycemia conditions that can occur due to impaired insulin secretion, insulin sensitivity or both. Semut Jepang (SJ) are used by people of Indonesians as a drug to reduce blood sugar levels, but have not been scientifically studied as antidiabetic. Therefore, this study aims to examine the antidiabetic activity of Japanese ant powder in mice. Method: The study was carried out using the antihyperglycemic method in mice induced by alloxan. In the antihyperglycemic method in alloxan induced mice, mice were divided into 6 groups, namely 1% normal Na CMC control group (not alloxan induced), 1% Na CMC pain control group (alloxan induced), glibenclamide 5 mg / kg bw comparison group, and 3 test groups were given Japanese ant powder with a dose of 9 mg / kg bw (SJ 9), 45 mg / kg bw (SJ 45), and 90 mg / kg bw (SJ 90). Blood glucose levels were measured on the first day, day 3, day 7, and day 14. Results: The use of SJ 45 and SJ 90 were better in lower blood glucose compared to the glibenclamide comparison group. Conclusion: Japanese ant powder at doses of 45 and 90 mg / kg bw give an antidiabetic effect that is better than glibenklamid 5 mg / kg bw in reducing blood glucose levels in mice induced by alloxan. Keyword : Semut jepang powder, diabetes mellitus, blood glucose level